2018
DOI: 10.3389/fneur.2018.00591
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study in Vestibular Neuritis: Involvement of the Host Factor for HSV-1 Replication

Abstract: Objective: In order to identify genetic variants associated with vestibular neuritis, a common cause of peripheral vertigo with a potential causative link to the reactivation of herpes simplex type 1 (HSV-1), we conducted a genome-wide association study.Methods: Association was assessed using approximately 8 million variants. 131 patients with vestibular neuritis and 2,609 controls of European ancestry were included.Results: Genome-wide associations with vestibular neuritis were detected in 4 regions containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 49 publications
0
29
0
5
Order By: Relevance
“…A genome-wide association study (GWAS) in 131 AUV patients and 2,609 controls was recently performed. 18 The authors noted that this was a very small number of cases for GWAS analysis, but found associations in regions that were considered to be involved in viral disorders and insulin metabolism. The findings also support the general notion of both viral and vascular contributions to AUV presentations.…”
Section: Acute Unilateral Vestibulopathy (Vestibular Neuritis)mentioning
confidence: 99%
“…A genome-wide association study (GWAS) in 131 AUV patients and 2,609 controls was recently performed. 18 The authors noted that this was a very small number of cases for GWAS analysis, but found associations in regions that were considered to be involved in viral disorders and insulin metabolism. The findings also support the general notion of both viral and vascular contributions to AUV presentations.…”
Section: Acute Unilateral Vestibulopathy (Vestibular Neuritis)mentioning
confidence: 99%
“…Datasets were combined to get a sufficient number of controls. For GWAS analysis, selected patients and controls were extracted from the combined dataset after global quality control [21].…”
Section: Overviewmentioning
confidence: 99%
“…All individuals included in this exploratory study were part of the PAGES sample 32 . All schizophrenia patients were recruited from the Munich area in Germany.…”
Section: Schizophrenia Patients and Healthy Controlsmentioning
confidence: 99%